Optimal Ni loading towards efficient CH4 production from H2 and CO2 over Ni supported onto fibrous SBA-15. (15th March 2019) - Bukhari, S.N.; Chong, C.C.; Setiabudi, H.D.; Ainirazali, N.; Aziz, M.A.A.; Jalil, A.A.; Chin, S.Y.
Abstract: The transformation of SBA-15 into fibrous type SBA-15 (F-SBA-15) as well as the influence of Ni loadings (1, 3, 5, and 10 wt%) towards an efficient CH4 production from H2 and CO2 were explored. The synthesized catalysts were characterized using XRD, BET, ICP-MS, FTIR, FESEM-EDX, TEM, and in-situ FTIR adsorbed pyrrole. Increasing Ni loadings onto F-SBA-15 support promoted excellent performance towards CO2 methanation. The efficacy in CO2 methanation over Ni/F-SBA-15 increased with a sequence of 1%Ni/F-SBA-15 < 3%Ni/F-SBA-15 < 5%Ni/F-SBA-15 ≈ 10%Ni/F-SBA-15, indicating the superior performance and stability of 5%Ni/F-SBA-15. The increasing trend was due to the fibrous morphology of support which enhanced the quantity of SiONi bond, triggered better Ni dispersion, strengthen metal-support interaction, and increased the basicity. However, higher Ni loadings (10 wt%) onto F-SBA-15 slightly declined the performance and stability of CO2 methanation due to the limited spaces for substitution of Ni species with the silanol groups of F-SBA-15 upon the bulk Ni phase, poorer Ni dispersion, weaker metal-support interaction, and lower basicity. The new finding of combination between fibrous SBA-15 (F-SBA-15) with an optimum Ni loading contributed towards an outstanding performance and thus could be applied in various applications. Graphical abstract: Image 1 Highlights: CO2 methanation was highly influenced by Ni loadings (1-10%) onto F-SBA-15. Efficiency of CO2 methanation; 1% < 3% < 5% ≈ 10%Ni. 5%Ni/F-SBA-15 exhibited superior performance and longer stability. Key factors: well-dispersed Ni, strong Si-O-Ni, and high active basic sites. NiO agglomeration and coke deposition were prominent at high Ni loading (10%).